2009
DOI: 10.1111/j.1365-2621.2009.02105.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying process on lemon verbena (Lippia citrodora Kunth) aroma and infusion sensory quality

Abstract: Lemon verbena leaves are used as herbal infusion due to their aromatic, digestive and antispasmodic properties. The aim of the present study was to determine the sensory quality of lemon verbena infusions prepared with fresh leaves, dried leaves at 30°C and 60°C. Infusion aroma and taste was determined through a trained sensory panel and an electronic nose (e-nose). Infusion acceptability was evaluated through a consumer test. All drying treatments on day 0 were grouped together regarding the e-nose determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…For each application, however, technical problems have to be solved for implementation on-line. One interesting feature for the future would be to have a fully automated platform of different kinds of sensors to monitor the vital information needed for the characterizing the quality of the raw material, process or product (Infante et al, 2010). Odor and taste sensors would make up an important part of such a multisensor system.…”
Section: Resultsmentioning
confidence: 99%
“…For each application, however, technical problems have to be solved for implementation on-line. One interesting feature for the future would be to have a fully automated platform of different kinds of sensors to monitor the vital information needed for the characterizing the quality of the raw material, process or product (Infante et al, 2010). Odor and taste sensors would make up an important part of such a multisensor system.…”
Section: Resultsmentioning
confidence: 99%
“…Rodrigo et al studied the effect of drying on lemon verbena aroma and infusion sensory quality by a trained sensory panel and an electronic nose (e-nose); results showed that an e-nose can be used as a reliable tool for characterizing the quality of aromatic herbs [24] .…”
Section: Biomimetic Systemsmentioning
confidence: 99%
“…The volume used was 200 mL of water at 100°C, which was poured over the extracts. The infusion time established was 10 min for both leaves and stems, since higher infusion periods are not indicated for preparation of teas (Infante et al, 2010;Koch et al, 2012).…”
Section: Preparation Of Infusionsmentioning
confidence: 99%